Production and evaluation of vaccines employing Pasteurella multocida A:1 grown under different growth conditions - Raja Gopal R (Department of Microbiology, College of Veterinary and Animal Sciences, 2007)
A research work was undertaken to prepare effective vaccines against P. multocida grown under different conditions and their immunopotency assessed in one month old ducklings. The purity of the Pasteurella multocida A: 1 strain (DP1) was confirmed as per standard procedures. Pathogenicity of the isolate was assessed in six to eight weeks old mice. The isolate killed the intraperitoneally inoculated mice within eight hours and within 24 h when injected by subcutaneous route. The organism was grown in different media to assess the amount of capsular material produced. The media employed were DSA, DSA supplemented with 10 per cent FBS and DSA supplemented with 10 per cent FBS and 0.5 per cent yeast extract. The capsule enhancement was measured by capsule demonstration using Maneval staining and by characterization of crude capsular extract. The capsules of the organisms grown in capsule enhancement media when demonstrated using Maneval staining were discernibly larger and denser, when compared to the organisms grown in DSA alone. The capsular polysaccharides increased by approximately 1.6 times when the organism was grown in capsule enhancement media containing 10 per cent FBS and by about 2.06 times when grown in media supplemented with FBS and yeast extract. The potential of the organism to form in vitro biofilm was assessed by growing the organism in nutrient restricted conditions. The organism was grown in 0.32 per cent TSB supplemented with an inert substrate called bentonite clay, for the bacteria to attach and colonize. For quantification of biofilm, plate count by spread plate method was employed and the results showed that the biofilm cells reached a peak on the third day of incubation with an average count of 1.54 ×106 CFU/g of bentonite clay while the planktonic cells were found to be maximum on day one post inoculation, with a peak count averaging about 8.10 ×108 CFU/ml of the broth. Maneval staining of late logarithmic phase of three day old biofilm culture revealed heavily capsulated cells of P. multocida attached as large aggregates and appearing as chains of coccobacillary cells. Also they appeared as a meshwork of aggregated and chain forming cells. The capsular polysaccharide estimation of biofilm cells revealed a 3.25 times increase over the planktonic bacteria grown in DSA alone. The biofilm cells on nutrient agar after 24 h at 37°C produced some colony morphotypes characterized by radiating strands from centre to periphery and wavy margin. Median lethal dose (LD50) of P. multocida when determined in one month old ducklings was 23 cells. In the present study, it was unable to arrive at the median lethal dose in six month old ducks as only one duck died after 48 h of virulent challenge. Oil adjuvant formalin inactivated bacterin vaccines were prepared from DP1 grown in TSB, capsule enhancement medium and under biofilm mode and performed the sterility, safety and potency tests of the vaccine employing standard procedures. A total of 160 four week old ducklings were divided into four groups with 40 birds in each group and the first three groups were vaccinated with ordinary bacterin, capsule enhanced bacterin and biofilm vaccine respectively. The fourth group served as control. The birds were vaccinated with 0.5 millilitre of vaccine intramuscularly in the thigh region. Blood was collected from all the ducks pre-vaccination, at weekly intervals upto 28th day post PV and on day 42 PV by cardiac puncture or by jugular venipuncture. Passive haemagglutination using GA-SRBC sensitized with sonicated antigen of DP1 was used to measure the humoral immune response. The IHA titres obtained for biofilm vaccine group on day 14 was very much higher than the other two groups. The antibody titre was observed from day seven onwards for all the groups. All the vaccine groups have shown significant difference from the control group at all the stages of the study. Groups I and II were having no significant difference in their mean titres during the entire study. On homologous challenging, biofilm vaccine gave higher protection rates of 70 and 90 per cent than the 60 and 80 per cent protection rates of ordinary and capsule enhanced bacterins, when challenged with 200 and 100 LD50 doses respectively. Biofilm vaccine was proved to be the best among the three vaccines tried. The capsule enhanced vaccine did not provide any additional advantage over the ordinary bacterin vaccine. Elaborate field trials are to be done before advocating the vaccine for commercial use.